Construction of in situ Access System for Marine Genetic Resources Beyond National Jurisdiction - Yao Shi (Law and Economy, 2022)
The international legally binding instrument under the United Nations Convention on the Law of the Sea (UNCLOS) on the conservation and sustainable use of marine biological diversity beyond areas of national jurisdiction (BBNJ agreement) being negotiated, there has been a great controversy over which regime should be followed for in situ access to marine genetic resources (MGRs) beyond national jurisdiction. System of free access is not conducive to the tracking of MGRs, and licence system may undermine the innovative capacity of research institutions because of the complexity of the procedures. Since in situ access to genetic resources is marine scientific research (MSR), the notification system for marine scientific research could be used to construct a regime for in situ access to MGRs beyond national jurisdiction. The adoption of an implied consent system and the use of the International Seabed Authority (ISA) and clearing-house mechanism as an approval body will help to improve the establishment of a system for in situ access to MGRs.